The efficacy and safety of a homeopathic gel in the treatment of acute low back pain: a multi-centre, randomised, double-blind comparative clinical trial - Stam, C; Bonnet, MS; van Haselen, RA (British Homeopathic Journal, 2001)
Acute low back pain is a very common condition in Western industrialised countries. In most cases analgesics or topical medications are prescribed at first encounter with the general practitioner (GP).The aim of this study was to investigate whether the homeopathic gel Spiroflor SRL® gel (SRL) is equally effective and better tolerated than Cremor Capsici Compositus FNA (CCC) in patients with acute low back pain.A multi-centre, randomised, double-blind, controlled clinical trial was conducted in the practices of 19 GPs in the districts of Bristol and Manchester, UK. One hundred and sixty-one subjects suffering from acute low back pain were treated for one week either with SRL or with CCC. Pain was scored on a 100 mm visual analogue scale (VAS). Main efficacy parameter VAS reduction was compared between treatments. Evaluation of safety was primarily based on the number of subjects with adverse events (AEs), withdrawals due to an AE and adverse drug reactions (ADRs).The mean difference between the VAS reduction in the SRL group and the CCC group adjusted for VAS at baseline and age was −0.6 mm (90%CI=−6.5–5.3 mm). Fewer subjects in the SRL group (11%) experienced an AE than in the CCC group (26%). The same applies to the number of subjects with an ADR (3/81=4% vs 18/74=24%) and the number of subjects withdrawn due to an ADR (0/81=0% vs 8/74=11%).In conclusion, SRL and CCC are equally effective in the treatment of acute low back pain, however, SRL has a better safety profile. Spiroflor SRL® gel is preferable to Capsicum-based products for the topical treatment of low back pain, because of the lower risk of adverse effects.
Keywords: Capsici Oleoresin; clinical trials; homeopathy; Ledum palustre L; low back pain; Rhus toxicodendron; Symphytum officinale L